MicroRNA-223 is involved in the pathogenesis of atopic dermatitis by affecting histamine-N-methyltransferase - Jia, Hui-Zhen; Liu, Sheng-Lin; Zou, Yan-Fen; Chen, Xiao-Fan; Yu, Lin; Wan, Jun; Zhang, Hong-Yu; Chen, Qi; Xiong, Yi; Yu, Bo; Zhang, Wei (Cellular and Molecular Biology, 2018)
Atopic dermatitis (AD) is one of the most prevalent skin diseases around the world. Excessive histamine plays a critical role as an inflammatory factor in the pathogenesis of AD. Deregulated microRNAs (miRNAs) were involved in atopic dermatitis by targeting various genes. MiR-223 had been reported to play a vital role in hematopoiesis. In this study, we identified upregulated miR-223 in the whole blood cells of a large group of AD patients. What's more, we found for the first time that one of the major histamine degradation enzymes, histamine-N-methyltransferase (HNMT), was increased in AD patients and AD model mice. Although there was one miR-223 binding site in the 3'- untranslated region of the HNMT gene, HNMT were not inhibited by miR-223. Taken together, it suggested that miR-223 participates in AD through upregulating HNMT indirectly to degrade the excessive histamine.